Assessing the repeatability of reflection seismic data in the presence of complex near-surface conditions CO2CRC Otway Project, Victoria, Australia - Al-Jabri, Yousuf; Urosevic, Milovan (CSIRO Publishing, 2010)
This study utilises repeated numerical tests to understand the effects of variable near-surface conditions on time-lapse seismic surveys. The numerical tests were aimed at reproducing the significant scattering observed in field experiments conducted at the Naylor site in the Otway Basin for the purpose of CO2 sequestration. In particular, the variation of elastic properties of both the top soil and the deeper rugose clay/limestone interface as a function of varying water saturation were investigated. Such tests simulate the measurements conducted in dry and wet seasons and to evaluate the contribution of these seasonal variations to seismic measurements in terms of non-repeatability. Full elastic pre-stack modelling experiments were carried out to quantify these effects and evaluate their individual contributions. The results show that the relatively simple scattering effects of the corrugated near-surface clay/limestone interface can have a profound effect on time-lapse surveys. The experiments also show that the changes in top soil saturation could potentially affect seismic signature even more than the corrugated deeper surface.Overall agreement between numerically predicted and in situ measured normalised root-mean-square (NRMS) differences between repeated (time-lapse) 2D seismic surveys warrant further investigation. Future field studies will include in situ measurements of the elastic properties of the weathered zone through the use of ‘micro Vertical Seismic Profiling (VSP)’ arrays and very dense refraction surveys. The results of this work may impact on other areas not associated with CO2 sequestration, such as imaging oil production over areas where producing fields suffer from a karstic topography, such as in the Middle East and Australia.